Autophagy Upregulation and Apoptosis Downregulation in DAHP and Triptolide Treated Cerebral Ischemia. (2nd February 2015) - Yang, Yang; Gao, Keqiang; Hu, Zhiying; Li, Weiyun; Davies, Henry; Ling, Shucai; Rudd, John A.; Fang, Marong
Abstract : It has previously been demonstrated that ischemic stroke activates autophagy pathways; however, the mechanism remains unclear. The aim of this study is to further investigate the role that autophagy plays in cerebral ischemia. 2, 4-diamino-6-hydroxy-pyrimidine (DAHP), for its nitric oxide synthase (NOS) inhibiting neuroprotective effect, and triptolide (TP), for its anti-inflammatory property, were selected to administer pre middle cerebral artery occlusion (MCAO). The drugs were administered 12 hours prior to MCAO. Both magnetic resonance imaging (MRI) and 2, 3, 5-triphenyltetrazolium chloride (TTC) staining showed that the drugs reduce the area of infarction. Immunoblotting analysis revealed increases in Beclin-1 and myeloid cell leukelia-1(Mcl-1) in treated rats. This could be a contributing factor to the reduction in autophagy induced damage. Immunochemistry and western blot showed that mTOR expression in treated rats was marginally different 24 h after injury, and this could also be significant in the mechanism. Furthermore, terminal deoxynucleotidyl transferase- (TdT-) mediated dUTP nick end labeling (TUNEL) staining proved that the drugs are effective in reducing apoptosis. The upregulation of Beclin-1 and Mcl-1 and downregulation of Bcl-2, caspase-3, and the Bcl-2/Beclin-1 ratio infer that the neuroprotective effect of DAHP and TP act via the mediation of autophagy and apoptosis pathways.